Preparation method and application of nitrogen and oxygen double-doped porous carbon loaded graphite felt electrode
Through electrochemical deposition and carbonization treatment technology, a porous carbon-loaded graphite felt electrode with dual doped nitrogen and oxygen is prepared, which solves the problem of insufficient performance of traditional electrodes under high current density, achieves high energy efficiency and long-term stability, and promotes the high performance development of VRFB electrodes.
Patent Information
- Application Number
- CN202510049467.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Traditional VRFB electrode materials such as carbon felt and graphite felt are insufficient when operating at high current density, resulting in low energy efficiency and high system cost, and traditional MOF synthesis methods are complex to operate and uneven layer growth.
Electrochemical deposition technology is used to uniformly deposit the ZIF-8 parent on the surface of the graphite felt fibers, and then nitrogen and oxygen doped porous carbon-loaded graphite felt electrodes (ZIF-8-C-GF) are prepared by carbonization to enhance the specific surface area and electrochemical activity of the electrode.
The high energy efficiency (85.77%) and good long-term stability of VRFB at a current density of 100 mA cm-2 are achieved, with a peak power density of 356 mW cm-2, providing a high-performance, scalable VRFB electrode solution.
Smart Images

Figure CN119786627A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and particularly relates to a preparation method and application of a nitrogen and oxygen doped porous carbon-loaded graphite felt electrode. Background Art
[0002] In recent years, the power generation of renewable energy sources such as solar and wind power has shown exponential growth. However, the mismatch between these volatile and intermittent renewable energy sources and grid demand has led to a large amount of energy waste. To solve this problem, large-scale energy storage technology has become an attractive solution. Among them, redox flow batteries (RFBs) have shown great development potential in various application scenarios due to their unique advantage of being able to separate energy storage from power output. In particular, all-vanadium redox flow batteries (VRFBs), as a representative of RFB technology, have become a popular choice due to their long life, high safety and flexible design. However, their high initial investment cost limits their widespread application in the energy market. An effective way to reduce costs is to increase the operating current density of VRFBs while maintaining high energy efficiency (EE), thereby reducing the volume of the system stack and optimizing economics.
[0003] In VRFBs, redox reactions mainly occur at the interface between the electrode and the electrolyte. Therefore, the surface physical structure and electrochemical properties of the electrode fibers play a crucial role in the performance of the battery. Specifically, the physical structure of the fiber surface affects the transport of electrons, ions, and substances, while the electrochemical properties directly affect the rate of redox reactions, which together affect activation loss, resistance loss, and concentration loss. Currently, the most commonly used electrode materials are carbon felt (CF) or graphite felt (GF) because of their high conductivity and good chemical stability. However, VRFBs using pristine CF or GF as electrodes can usually only operate at low current densities, which is mainly attributed to their low electrochemical activity and limited specific surface area (SSA). Metal-organic frameworks (MOFs) are porous coordination polymers with high specific surface area, tunable pore structure, and broad application prospects. Carbon materials derived from MOFs have been widely used in energy storage devices and have become an ideal choice for high-performance electrode materials. These carbon materials retain the characteristics of the parent MOFs and usually have a large specific surface area (SSA) and high porosity. In addition, by regulating the carbonization temperature, the physical structure and surface chemical properties of carbon materials can be optimized, thereby improving the charge transfer efficiency, electrical conductivity and mass transfer capacity, and accelerating the redox reaction process. Studies have shown that a variety of MOF materials (such as Zn-MOF, Co-MOF, Ni-MOF, Sn-MOF, Zr-MOF and W / Zr-MOF) can significantly improve the reaction kinetics of vanadium species, thereby giving VRFB excellent performance. However, the traditional in-situ synthesis method has problems such as complex operation and uneven growth of the MOF layer on the fiber surface, which limits the full performance of the battery. This challenge needs to be solved urgently.
[0004] The present invention uses electrochemical deposition (ED) technology to quickly achieve uniform and dense MOF deposition on the surface of the electrode fiber. Subsequently, nitrogen and oxygen doped porous carbon-supported graphite felt (ZIF-8-C-GF) was prepared by carbonization treatment. This dual-doping functionalization strategy significantly improves the hydrophilicity and electrochemical activity of the electrode surface, while optimizing the mass transfer performance of the electrode by utilizing the high porosity of MOF. VRFB based on ZIF-8-C-GF electrode is 100 mA cm -1 The electrode exhibited excellent performance at a current density of 100 mA cm-1, with an energy efficiency (EE) of 85.77%. In addition, the electrode showed good stability in long-term operation. -2 After 500 cycles under the same conditions, the energy efficiency remains above 75.55%. At the same time, the VRFB can achieve 356 mW cm -2 The peak power density provides new directions and possibilities for the development of high-performance and scalable VRFB electrodes. Summary of the invention
[0005] The first object of the present invention is to provide a method for preparing a nitrogen and oxygen doped porous carbon supported graphite felt electrode, comprising the following steps: S1. Preparation of ZIF-8 mother solution Dissolving zinc acetate and 2-methylimidazole in methanol respectively, followed by stirring and ultrasonic treatment; then mixing and stirring the two solutions to form a uniform mother solution; S2. Preparation of ZIF-8@GF by electrochemical deposition The graphite felt was cut into sheets of 2×3 mm as the working electrode, and the zinc foil was cut into the same size as the counter electrode; the two electrodes were simultaneously immersed in the mother solution obtained in step S1 and subjected to electrodeposition treatment to prepare ZIF-8@GF. The prepared ZIF-8@GF was washed with methanol to remove unreacted precursors and then dried in an oven at 60 °C.
[0006] S3. Preparation of ZIF-8-C-GF The ZIF-8@GF obtained in step 2 was carbonized by high-temperature calcination in an argon flow, and then the prepared material was immersed in a 10% H2SO4 solution for 6 h at room temperature to remove residual zinc; the sample was then washed with water and dried to obtain ZIF-8-C-GF.
[0007] Further, in step S1, 2-methylimidazole and Zn 2+ The molar ratio is 2:1.
[0008] Furthermore, the electrodeposition treatment condition in step S2 is electrodeposition at room temperature with a current of 5 mA for 40 minutes.
[0009] Furthermore, in step S3, the high temperature calcination and carbonization process is specifically performed as follows: ZIF-8@GF synthesized in step S2 is heated to 100 mL min -1 Under argon flow, 5 °C min -1 The sample was heated to 700-900 °C at a heating rate of 100 °C and carbonized for 0.5 h.
[0010] The present invention also provides application of the nitrogen and oxygen dual-doped porous carbon-loaded graphite felt electrode in a redox flow battery.
[0011] Beneficial technical effects of the present invention: The present invention successfully synthesized a nitrogen and oxygen doped MOF-derived porous electrode by combining an electrochemical deposition strategy with a pyrolysis method. This method can evenly load ZIF-8-derived carbon on graphite felt, thereby increasing the specific surface area of the electrode, and significantly enhances the electrode's V 3+ / V 2+ and VO 2+ / VO2 + The VRFB assembled with ZIF-8-C-GF as positive and negative electrodes exhibited electrochemical activity at 100 mA cm -2 At a current density of 1.3 Å, a high energy efficiency of over 85.77% can be achieved, and good long-term stability of 500 cycles can be achieved. The present invention provides an efficient and reliable method for developing high-performance VRFB electrodes and opens up a new direction for commercial electrode design. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Schematic diagram of the synthesis route of the ZIF-8-C-GF electrode synthesized in Example 1.
[0013] Figure 2 SEM images of (a) pristine GF, (b) ZIF-8@GF, and (c) ZIF-8-C-GF.
[0014] Figure 3 EDS mapping images of ZIF-8-C-GF: (a) carbon, (b) nitrogen and (c) oxygen elements.
[0015] Figure 4 XRD patterns of original GF, ZIF-8@GF and ZIF-8-C-GF.
[0016] Figure 5 Raman spectra of original GF and ZIF-8-C-GF.
[0017] Figure 6 Nitrogen adsorption–desorption isotherms of pristine GF, ZIF-8@GF, and ZIF-8-C-GF.
[0018] Figure 7 Pore size distribution curves of (a) ZIF-8-C-GF and (b) pristine GF.
[0019] Figure 8 The contact angle of the original GF (152.1°) (a) and the contact angle of ZIF-8-C-GF (105.5°) (b).
[0020] Fig. 9 Schematic diagram of the wettability of the original GF (a) and the wettability of ZIF-8-C-GF (b).
[0021] Fig.10 (a) C1s XPS spectra of pristine GF and ZIF-8-C-GF, (b) N1s XPS spectra, and (c) O1s XPS spectra.
[0022] Fig.11Cyclic voltammetry (CV) curves of pristine GF and ZIF-8-C-GF at a scan rate of 2 mV / s: (a) positive electrode reaction, (b) negative electrode reaction, and (c) bar chart of the Ipa / -Ipc ratio of CV curves in the positive and negative reactions.
[0023] Fig.12 Nyquist plots of pristine GF and ZIF-8-C-GF at (a) positive electrode and (b) negative electrode.
[0024] Fig.13 For different samples at V 3+ / V 2+ and VO 2+ / VO2 + The charge transfer resistance (R CT ).
[0025] Fig.14 For different electrodes at 100 mA cm -2 VRFB charge and discharge curves under current density.
[0026] Fig.15 Coulombic efficiency (CE) (a), voltage efficiency (VE) (b), and energy efficiency (EE) (c) of pristine GF and ZIF-8-C-GF at different current densities.
[0027] Fig.16 CE, VE, and EE of pristine GF, ZIF-8-C-GF-700 °C, ZIF-8-C-GF-800 °C, and ZIF-8-C-GF-900 °C at different current densities.
[0028] Fig.17 VRFB polarization and power density curves of different electrodes.
[0029] Fig.18 VRFB of different electrodes at 100 mA cm -2 The cycle performance results graph below. DETAILED DESCRIPTION
[0030] Example 1 S1. Preparation of mother solution for synthesis of ZIF-8@GF 0.55 g of zinc acetate and 0.41 g of 2-methylimidazole (2-MIM) were dissolved in 20 mL of methanol, stirred and ultrasonicated. The two solutions were then mixed and stirred to form a homogeneous mother liquor. 2+ The molar ratio is 2:1.
[0031] S2. Preparation of ZIF-8@GF by electrochemical deposition The graphite felt was cut into 2×3 mm sheets as the working electrode, and the zinc foil was cut into the same size as the counter electrode. The two electrodes were immersed in the mother solution at the same time and electroplated at a current of 5 mA for 40 minutes at room temperature to obtain ZIF-8@GF. The obtained ZIF-8@GF was washed with methanol to remove the unreacted precursors and then dried in an oven at 60 °C.
[0032] S3. Preparation of ZIF-8-C-GF The synthesized ZIF-8@GF was heated in an argon flow (50 mL min -1 ) at 5 °C min -1 The sample was heated to 800 °C at a heating rate of 100 °C and kept for 0.5 h for carbonization. Subsequently, the obtained material was immersed in a 10% H2SO4 solution at room temperature for 6 h to remove the residual zinc. Then, the sample was washed with water and dried to obtain ZIF-8-C-GF.
[0033] Example 2 The difference between Example 2 and Example 1 is that the calcination and carbonization temperature in S3 is 700°C, and the other conditions are exactly the same.
[0034] Example 3 The difference between Example 3 and Example 1 is that the calcination and carbonization temperature in S3 is 900°C, and the other conditions are exactly the same.
[0035] Comparative Example 1 Comparative Example 1 is original graphite felt. As a control, the original graphite felt is also subjected to the same heat treatment and acid treatment as Example 1.
[0036] The samples prepared in Example 1 and Comparative Example 1 were characterized: (1) Scanning electron microscopy characterization The microstructure of the samples was observed by scanning electron microscopy (SEM SU3500) with a scanning voltage of 20 kV.
[0037] Figure 2 ac show the scanning electron microscopy (SEM) images of pristine graphite felt (GF), ZIF-8 coated graphite felt (ZIF-8@GF), and carbonized ZIF-8 derived porous carbon coated graphite felt (ZIF-8-C-GF), respectively. Figure 2 In a, the GF fiber has a smooth surface and a diameter of approximately 8 µm. Figure 2 b shows that the GF surface is uniformly covered with a layer of ZIF-8 with a thickness of about 1.5 μm. Since ZIF-8 shrinks in volume during the carbonization process, Figure 2 The diameter of ZIF-8-C-GF fibers in c is reduced to about 9 μm (2) Energy dispersive X-ray spectroscopy (EDS) characterization The types and distribution of elements in the samples were analyzed by energy dispersive X-ray spectroscopy (EDS).
[0038] Energy dispersive X-ray spectroscopy (EDS) analysis confirmed the doping of nitrogen (N) and oxygen (O) elements onto the fiber surface ( Figure 3 ac), these elements will serve as reaction sites to promote the redox reaction of vanadium ions.
[0039] (3) X-ray diffraction (XRD) pattern characterization X-ray diffraction (XRD) characterizations were measured using a Rigaku Smartlab 3 X-ray powder diffractometer equipped with a copper sealed tube (λ = 1.54178 Å) and performed at room temperature.
[0040] X-ray diffraction (XRD) pattern ( Figure 4 ) shows that ZIF-8@GF has the characteristic peaks of bulk ZIF-8. After calcination, ZIF-8 decomposes and transforms into porous carbon, and a diffraction peak appears at the graphite (002) crystal plane close to 26.3°. Therefore, the characteristic peaks of ZIF-8 are not observed in the XRD spectrum of ZIF-8-C-GF, indicating that ZIF-8 first nucleates and grows on the surface of graphite felt fibers, and then decomposes to form porous carbon during calcination.
[0041] (4) Raman spectroscopy characterization In order to further analyze the structure of the carbon material, Raman spectroscopy was performed ( Figure 5 ), the laser wavelength was 532 nm. All samples were detected at 1345 cm -1 and 1590 cm -1 Two significant peaks appeared at the ZIF-8-C-GF, corresponding to the D band and G band of typical carbon materials. The intensity ratio of the D band and the G band (ID / IG) reflects the disorder degree of the carbon material. The ID / IG ratio of ZIF-8-C-GF is 0.97, which is higher than 0.84 of the original GF, indicating that there are more defects in ZIF-8-C-GF and it can provide more active sites.
[0042] (5) Nitrogen adsorption and desorption isotherm test Nitrogen adsorption and desorption isotherms were measured using an AutosorbiQ automatic gas adsorption analyzer, and the specific surface area and pore size distribution were calculated by the Brunauer-Emmett-Teller (BET) method and Barret-Joyner-Halenda (BJH) analysis.
[0043] BET analysis at 77 K ( Figure 6) showed that the specific surface area of the original GF increased from 1.923 m 2 / g increased to 11.971 m / g for ZIF-8-C-GF 2 / g. The higher specific surface area provides more active sites for the charge transfer of vanadium ions and promotes its charge transfer kinetics. In addition, the pore size distribution before and after modification was calculated by the BJH method, such as Figure 7 As shown, the results indicate that the significant increase in mesopores facilitates the diffusion of vanadium ions.
[0044] (6) Contact angle test The contact angle was measured by a contact angle meter (Dataphysics-TP50). The hydrophilicity of the original GF and ZIF-8-C-GF was verified by testing the contact angle. Figure 8 Compared with the original GF, the contact angle of ZIF-8-C-GF is smaller, which is mainly attributed to the increase of N and O functional groups on its surface, which significantly improves the wettability of the material. In addition, immersion tests show that ZIF-8-C-GF can sink to the bottom of the water due to its hydrophilicity, while the original GF floats on the water surface due to its hydrophobicity ( Fig. 9 ). These results indicate that the excellent hydrophilicity of ZIF-8-C-GF can significantly increase its contact area with the electrolyte, thus helping to increase its electrochemically active surface area.
[0045] (7) X-ray photoelectron spectroscopy (XPS) characterization The elemental composition and chemical bonding of the pristine GF and ZIF-8-C-GF were characterized by X-ray photoelectron spectroscopy (XPS). Fig.10 a) After deconvolution, it shows two main peaks at 284.8 eV and 285.4 eV, corresponding to the C=C bond and the C-C bond, respectively. It is worth noting that an additional peak appears in the C1s spectrum of ZIF-8-C-GF at 287.9 eV, which is caused by the formation of CO and CN bonds. This result indicates that nitrogen and oxygen atoms are introduced after the decomposition of ZIF-8 and combine with the defective carbon to form nitrogen and oxygen functional groups. N1s spectra of pristine GF and ZIF-8-C-GF ( Fig.10 b) shows that no obvious nitrogen peaks were detected in the original GF, while four nitrogen species appeared in ZIF-8-C-GF: pyridinic nitrogen (398.7 eV), pyrrolic nitrogen (400.9 eV), graphitic nitrogen (401.9 eV) and oxidized nitrogen (402.3 eV). In addition, the O1s spectrum ( Fig.10 c) can be deconvoluted into two components, corresponding to C-OH and -COOH. These two oxygen functional groups can effectively promote the redox reaction of vanadium ions on the electrode surface.
[0046] Example 4 Electrochemical Performance Test Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to characterize the VO 2+ / VO2 + and V 3+ / V 2+ The electrochemical performance of the redox couple on pristine GF and ZIF-8-C-GF was evaluated. 2+ / VO2 + In the CV curve of the reaction ( Fig.11 a), ZIF-8-C-GF exhibits significantly enhanced electrochemical activity, with an anodic peak current density (Ipa) of 65 mA cm -2 , the cathode peak current density (-Ipc) is 40mAcm -2 , which are significantly higher than the 51 mA cm of the original GF. -2 and 26 mA cm -2 This is mainly due to the significant increase in the specific surface area (SSA) of the electrode surface after modification with ZIF-8 derivatives.
[0047] In V 3+ / V 2+ In the CV curve of the reaction ( Fig.11 b) The difference between the two materials is more obvious. The original GF does not show V 3+ Restore to V 2+ In contrast, an obvious reduction peak appeared in the CV curve of ZIF-8-C-GF, indicating that ZIF-8 derivatives can effectively promote the degradation of V 3+ / V 2+ The reduction reaction of the anode and cathode is inhibited and the hydrogen evolution reaction is suppressed. In addition, the ratio of the anode to cathode peak current is closer to 1 ( Fig.11 c) ZIF-8-C-GF in VO 2+ / VO2 + and V 3+ / V 2+ It showed higher reversibility in the reaction, which was significantly better than the original GF.
[0048] The EIS curves of different electrodes are as follows: Fig.12 a and 12b. The charge transfer resistance (R CT ). ZIF-8-C-GF as the positive and negative electrodes CT 1.06 Ω·cm 2 and 2.53 Ω·cm 2 , while the original GF is used as the positive and negative R CT 2.86 Ω·cm 2 and 159.3 Ω2 ( Fig.13 Compared with the original GF, ZIF-8-C-GF exhibited significantly lower R CT , indicating that it has faster charge transfer kinetics and excellent electrochemical activity. These results are consistent with the CV test results, further proving that the porous carbon layer derived from ZIF-8 increases the specific surface area of the electrode through the surface N and O functional groups, thereby effectively accelerating the conversion process of vanadium ions.
[0049] To evaluate the battery performance, VRFBs were assembled using ZIF-8-C-GF and pristine GF, respectively. Fig.14 Demonstrated at 100mAcm -2 Figure 3. Charge-discharge curves at different current densities. Compared with the VRFB using pristine GF, the VRFB using ZIF-8-C-GF exhibits a lower charge onset plateau and a higher discharge onset plateau, which is attributed to its lower cell polarization. -2 Their charge and discharge performances were evaluated at different current densities. The coulombic efficiency (CE) of both VRFBs exceeded 95%, indicating that they have good sealing properties ( Fig.15 a). Polarization is a key factor affecting battery voltage efficiency (VE) and energy efficiency (EE) ( Fig.15 b, c). The experimental results show that at 100 mA cm -2 At a current density of 200 mA cm-1, the VRFB using ZIF-8-C-GF achieved a voltage efficiency of 87.02% and an energy efficiency of 85.77%, while the VRFB using the original GF achieved 78.89% and 76.32%, respectively. As the current density increased, the VRFB using the original GF could no longer work, while the VRFB using ZIF-8-C-GF could still operate stably and maintain high efficiency at 200 mA cm-1. -2 The energy efficiency was maintained at 73.37% under the condition of high temperature. This indicates that the ZIF-8-derived N and O dual-doped carbon coating significantly improves the charge transfer rate and the adsorption performance of vanadium ions by increasing the specific surface area of the electrode and increasing the active sites.
[0050] To further explore the effect of calcination temperature on electrode performance, experiments at different temperatures (700 °C, 800 °C, and 900 °C) were carried out. Fig.16 The battery performance data in a and 16b show that the material calcined at 800 °C exhibits the best performance. Fig.17 The polarization curves at 50% charge state are shown, and the results show that the VRFB using ZIF-8-C-GF has a smaller polarization than the VRFB using pristine GF. The peak power density of the VRFB using ZIF-8-C-GF reaches 356 mW cm-2 , which is significantly higher than the 210 mW cm of the original GF. -2 . Fig.18 The long-term cycling performance of VRFB was demonstrated. After 500 cycles, the VRFB using ZIF-8-C-GF still maintained a high energy efficiency (75.55%), indicating its good mechanical stability.
Claims
1. A method for preparing a nitrogen and oxygen doped porous carbon supported graphite felt electrode, comprising the following steps: S1. Preparation of ZIF-8 mother solution Dissolving zinc acetate and 2-methylimidazole in methanol respectively, followed by stirring and ultrasonic treatment; then mixing and stirring the two solutions to form a uniform mother solution; S2. Preparation of ZIF-8@GF by electrochemical deposition The graphite felt was cut into sheets of 2×3 mm as the working electrode, and the zinc foil was cut into the same size as the counter electrode; the two electrodes were simultaneously immersed in the mother solution obtained in step S1, and an electrodeposition treatment was performed to prepare ZIF-8@GF, and the prepared ZIF-8@GF was washed with methanol to remove unreacted precursors, and then dried in an oven at 60°C; S3. Preparation of ZIF-8-C-GF The ZIF-8@GF obtained in step 2 was carbonized by high-temperature calcination in an argon flow, and the carbonized material was immersed in a H2SO4 solution at room temperature to remove residual zinc; the sample was washed with water and dried to obtain ZIF-8-C-GF.
2. The method for preparing the nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode according to claim 1, characterized in that: In step S1, 2-methylimidazole and Zn 2+ The molar ratio is 2:
1.
3. The method for preparing the nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode according to claim 1, characterized in that: In step S2, the electrodeposition treatment was performed under the conditions of 5 mA at room temperature for 40 minutes.
4. The method for preparing the nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode according to claim 1, characterized in that: In step S3, the high temperature calcination and carbonization process is as follows: ZIF-8@GF synthesized in step S2 is heated to 100 mL min -1 5 °C min under argon flow -1 The sample was heated to 700-900 °C at a heating rate of 100 °C and carbonized for 0.5 h.
5. The method for preparing the nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode according to claim 4, characterized in that: The calcination temperature is 800°C.
6. The method for preparing the nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode according to claim 4, characterized in that: The calcination temperature is 800°C.
7. Use of a nitrogen and oxygen dual-doped porous carbon-supported graphite felt electrode prepared by the preparation method according to any one of claims 1 to 6 in a redox flow battery.
Citation Information
Patent Citations
Method for preparing nitrogen-oxygen double-doped graded porous carbon material
CN109626374A
Monatomic catalyst composite electrode for all-vanadium redox flow battery as well as preparation and application of monatomic catalyst composite electrode
CN116314856A
Preparation method of zinc-based metal organic framework derived nitrogen-doped porous carbon electrode material
CN116789238A
Preparation method of network modified flow battery graphite felt positive electrode material constructed by loading MOFs (Metal-Organic Frameworks) material on conductive additive
CN119008977A
Electrode for secondary batteries containing high-density carbon defect structure and method of producing the same
US20210288303A1